1970
DOI: 10.1017/s0043174500078607
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Herbicides on Lateral Roots and Nut Quality of Pecans

Abstract: Trifluralina,a,a-trifluoro-2,6-dinitro-N,N-dipropyl-p-toluidine) applied at 1.12 kg/ha inhibited lateral root development on field-grown pecan(Carya illinoensis(Wang.) K. Koch) seedlings. In a greenhouse study, inhibition of lateral roots, club-shaped radicles, and restricted penetration of tap roots resulted when pecans were planted in soil treated with 1.0 ppm trifluralin. When pecans were planted above soil treated with trifluralin, normal root development occurred only in the soil which had not been treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1972
1972
1990
1990

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The present experiments also showed high levels of accumulation of trifluralin in roots of intact peanut seedlings cultured at low tempera tures. Roots apparently are the more susceptible site of injury in plants (1,3,6). It appears probable that the in jury of trifluralin-treated peanut seedlings occurs under field conditions as a result of excessive trifluralin accumula tion in roots during cool periods.…”
Section: Hawxby Et Al : Trifluralin and Methazole In Peanutsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present experiments also showed high levels of accumulation of trifluralin in roots of intact peanut seedlings cultured at low tempera tures. Roots apparently are the more susceptible site of injury in plants (1,3,6). It appears probable that the in jury of trifluralin-treated peanut seedlings occurs under field conditions as a result of excessive trifluralin accumula tion in roots during cool periods.…”
Section: Hawxby Et Al : Trifluralin and Methazole In Peanutsmentioning
confidence: 99%
“…Trifluralin appears to inhibit lateral root growth by blocking cell division and causing irregularities in chromo some and nuclear behavior (2,3). Tap roots are not in hibited as greatly as lateral roots (1,6) WEED SCIENCE from the soil. The data of Kerchersid et al (5) indicated that less herbicide was taken up by tap roots than lateral roots since less trifluralin was taken up per gram of root tissue when young plants lacking lateral roots were trans planted to trifluralin-treated soil than when older seedlings with abundant lateral roots were used.…”
Section: Introductionmentioning
confidence: 99%
“…Trifluralin affects root morphology of susceptible plant seedlings by reducing root growth and causing swelling near the root tips, which is referred to as clubbing or tumor for mation (2,4,7). Roots of monocotyledons are more affected by trifluralin than those of dicotyledons (1).…”
Section: Introductionmentioning
confidence: 99%
“…Swelling of root tissue occurs in the region of maximum elongation (2) and root inhibition may occur within hours of exposure to trifluralin (14). Trifluralin may also inhibit the production of lateral roots (3,6,7). Oliver and Frans (9) suggested that lateral root inhibition along the tap root of cotton (Gossypium hirsutum L.) and soybean {Glycine max (L.) Merr.]…”
Section: Introductionmentioning
confidence: 99%
“…According to Probst et al (9), trifluralin is not translocated in significant amounts to the tops of plants. Trifluralin appears to act primarily in the root system (2,5,6), and it is possible that herbicides which do not translocate acropetally could accumulate in the roots under cool conditions.…”
Section: Introductionmentioning
confidence: 99%